2016
DOI: 10.21276/ijmrp.2016.2.3.029
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Spectrum of Uterus and Cervix in Hysterectomy Specimens

Abstract: Background: Hysterectomy is considered definite treatment of various pelvic pathologies like leiomyoma, dysfunctional uterine bleeding (DUB), chronic pelvic pain, endometriosis, adenomyosis, prolapse, and malignancies, since early twentieth century. In fact, it is the second most frequently performed major surgical procedure in females all over the world next to cesarean section.Numerous types of nonneoplastic and neoplastic lesions of uterus and cervix are commonly encountered in clinical practice. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…14 Eleven (2.31%) cases of endometrial carcinoma were encountered in the present study. This finding is close to that reported by Ankur et al 15 In the present study, myometrium was histologically normal in 210 (44.12%) cases and leiomyoma was the most common myometrial pathology, detected in 179 (37.61%) cases. These findings were comparable to that reported by Vani et al, they reported histologically normal myometrium in 44.28% and leiomyoma in 41.08% cases.…”
Section: Discussionsupporting
confidence: 92%
“…14 Eleven (2.31%) cases of endometrial carcinoma were encountered in the present study. This finding is close to that reported by Ankur et al 15 In the present study, myometrium was histologically normal in 210 (44.12%) cases and leiomyoma was the most common myometrial pathology, detected in 179 (37.61%) cases. These findings were comparable to that reported by Vani et al, they reported histologically normal myometrium in 44.28% and leiomyoma in 41.08% cases.…”
Section: Discussionsupporting
confidence: 92%
“…In a study by MacKenzie et al [13], abdominal hysterectomy was preferred in 79% of the cases and vaginal hysterectomy in 17% of the cases. Studies by Sachin et al [14], Pandey et al [15], Sujatha et al [16], and Gupta et al [17] revealed that the most common hysterectomy procedure was total abdominal hysterectomy. Data from the United Kingdom reveal that abdominal hysterectomy procedures are five to six times more common than vaginal hysterectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common benign pathology detected in hysterectomy specimens in many studies. 18,19,20,21 Adenomyosis is characterized by the presence of endometrial glands and stroma within the myometrium. Patients are typically pre-or peri-menopausal women who present with abnormal bleeding.…”
Section: Discussionmentioning
confidence: 99%